A2.8 Enhanced Neutrophil Extracellular Trap Formation in Rheumatoid Arthritis Patients is Correlated with High Levels of Rheumatoid Factor (RF). (25th February 2013) - Papadaki, Garyfalia; Choulaki, Christiana; Bertsias, George; Mitroulis, Ioannis; Verginis, Panayotis; Repa, Argyro; Raptopoulou, Amalia; Boumpas, Dimitrios; Sidiropoulos, Prodromos
Abstract : Background/Objectives: Neutrophils are the most abundant cell type identified in joints from patients with rheumatoid arthritis (RA), with a key role in inflammation and cartilage damage. Activated neutrophils form extracellular traps (NETs) with potent pro-inflammatory and immunostimulatory activity. Consequently, we sought to assess the role of NET release (NETosis) in RA pathogenesis and whether RA specific autoantibodies (rheumatoid factor [RF]) are correlated to this phenomenon. Materials/Methods: Peripheral blood neutrophils were isolated from active RA patients (n = 6) (Disease activity score, DAS28 > 5.1) and healthy control subjects (n = 7). NET formation from neutrophils, both spontaneous and following incubation with RA serum (n = 7) or synovial fluid (n = 7), was assessed by immunofluoresence microscopy, using co-staining with myeloperoxidase and 4', 6-Diamidino-2-phenylindole dihydrochloride (DAPI). The percentage of NET releasing cells was determined by examining 200 cells per sample in a double blind fashion. Extracellular DNA content was quantified by fluorescence spectrometry (picogreen) and NET fold increase was calculated based on the extracellular DNA content produced by healthy unstimulated neutrophils. Results: Freshly isolated neutrophils from the peripheral blood of RA patients underwent spontaneous NETosis at higher rates compared to healthy controls (12 ± 2.1% versus 3.2 ± 0.9%, p < 0.05). Notably, neutrophils isolated from RA synovial fluid exhibited even higher rates of NETosis. Incubation of healthy neutrophils with RA serum or synovial fluid induced NET release compared to the effect of normal serum (16 ± 2.5% and 9 ± 1.5%, versus 3.2 ± 0.7 p < 0.005). Moreover, quantification of the extracellular DNA content revealed that neutrophils from RF positive RA patients (n = 6) exhibited significantly increased spontaneous NET formation compared to RF negative patients (n = 8) (542 ± 115.2 ng/ml versus 199 ± 52.84 ng/ml, p = 0.008). Treatment of healthy neutrophils with either serum or synovial fluid derived from RF positive RA patients increased NETs compared to cells treated with normal serum (1.45 ± 0.19 and 4.85 ± 1.5 fold increase, p < 0.05). Inhibition studies are in progress to address the role of inflammatory cytokines (TNF-a, IL-6, IL-1b) and immune complexes in RA NETosis. Preliminary data show that NET induction in healthy neutrophils upon treatment with RA serum/synovial fluid may be mediated through Fcγ receptors. Conclusions: We found that neutrophils from RA patients have enhanced NET formation, driven by soluble factors found in RA sera and synovial fluid, and this is associated with presence of RF. Further studies will address whether NETs are involved in the initiation of adaptive immune responses in humans and in mouse model of arthritis, and whether suppression of NETosis may ameliorate arthritis in RA mouse models.